Management consultancy: Boundaries and knowledge in action - STURDY, Andrew (Institutional Knowledge at Singapore Management University, 2009)
Management consultants are typically seen as key mediators in the flow of management ideas. And yet little is known about exactly what happens when they work together with clients, behind closed doors in consulting projects. Do they really innovate or simply legitimate existing knowledge? This book presents research from a three year long 'fly-on-the-wall study' of consulting projects and challenges our taken for granted view of consultancy. It draws on and integrates theories of knowledge and social boundaries to reveal a picture of complex and shifting insider-outsider relationships. Here, the outsider or expert status of consultants in relation to their clients cannot be assumed in their day-to-day project interactions. Different actors, roles, and types of knowledge are involved in an interactive and dynamic process where various boundaries are constructed, reinforced, negotiated and transformed.